Fundamental financial accounting concepts / Thomas P. Edmonds, Frances M. McNair, Philip R. Olds, Edward E. Milam - Edmonds, Thomas P.; McNair, Frances M.; Olds, Philip R.; Milam, Edward E. (McGraw-Hill Irwin, 2013)
Enables students to understand how any given business event affects the financial statements. This title presents the financial statements model, which allows students to visualize the simultaneous impact of business events on the key financial statements (the income statement, the balance sheet, and the statement of cash flows).